Effectiveness of Aromatic Pandan and Golek Mango Leaves as Housefly (Musca Domestica) Repellents - Hepni, Hepni; Isnawati, Isnawati; Noraida, Noraida; A., Syarifudin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Houseflies are a vector that can transmit diarrheal diseases. Diarrheal disease is the leading cause of under-five mortality in Indonesia at 10.3%, so fly control is a necessity. One method of fly control is the use of vegetable repellent. This study aims to determine the relative effectiveness of repellent solutions derived from fragrant pandanus leaf (Pandanus amaryllifolius Roxb.) and mango golek leaf (Mangifera indica) against houseflies (Musca domestica). This research used a true experiment with a posttest only control group design. The sample houseflies (Musca domestica) with 270 flies in 3 repetitions. Data was analyzed using a two-way ANOVA test. The results showed a difference in repellent effectiveness of fragrant pandanus leaf solution and golek mango leaf solution. The difference in repellent power of fragrant pandanus leaf solution with a concentration of 5% by 25%, 10% by 25%, 15% by 37.5% and 20% by 50%. While golek mango leaf solution with a concentration of 5% by 50%, 10% by 50%, 15% by 62.5%, and 20% by 75%. There is a difference in repellent effectiveness. It is recommended that the community utilize the golek mango leaf solution as an environmentally friendly alternative to repel houseflies (Musca domestica).